Integration of Satellite and Blockchain Technology in Carbon Trade Marketing Model: Case Study of REDD+ Scheme in Bromo-Tengger-Semeru Protection Forest - Haryono, Haryono (West Science Agro, 2025)
This study explores the integration of satellite technology and blockchain platforms in the context of the REDD+ (Reducing Emissions from Deforestation and Forest Degradation) program of the Bromo-Tengger-Semeru Protection Forest. Through Geographic Information Systems (GIS) spatial analysis and blockchain modeling, the research develops a comprehensive carbon trade marketing model to address monitoring, transparency, and efficiency problems in carbon credit trade. Results indicate that GIS effectively identifies high-priority sites for conservation, while blockchain enables and maximizes carbon credit trade with smart contracts. Stakeholder comments underscore regulatory clarity, public engagement, and technical expertise in ensuring the optimal utilization of the model. The proposed convergence offers a cost-effective, scalable, and open-source solution to complement REDD+ implementation for promoting global efforts toward mitigation of climate change and sustainable development.